2018
DOI: 10.1186/s12969-018-0236-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 blockade in systemic juvenile idiopathic arthritis – achievement of inactive disease and remission (data from the German AID-registry)

Abstract: BackgroundSystemic juvenile idiopathic arthritis (sJIA) is a complex disease with an autoinflammatory component of unknown etiology related to the innate immune system. A major role in the pathogenesis has been ascribed to proinflammatory cytokines like interleukin-6 (IL-6), and effective drugs inhibiting their signaling are being developed. This study evaluates sJIA patients treated with the IL-6 inhibitor tocilizumab (TCZ) concerning clinical response rate, disease course and adverse effects in a real-life c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
0
22
1
1
Order By: Relevance
“…The relatively high usage of anti‐TNF in our cohort could be explained by their availability prior to anti‐IL agents (anti‐IL‐1 and anti‐IL‐6) and high percentage of patients with chronic arthritis in our cohort. The increased usage of anti‐IL‐1 and anti‐IL‐6 in sJIA patients recently provided significant improvement in sJIA treatment . In a routine practice, we use tocilizumab for patients resistant to standard treatment with predominantly joint involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high usage of anti‐TNF in our cohort could be explained by their availability prior to anti‐IL agents (anti‐IL‐1 and anti‐IL‐6) and high percentage of patients with chronic arthritis in our cohort. The increased usage of anti‐IL‐1 and anti‐IL‐6 in sJIA patients recently provided significant improvement in sJIA treatment . In a routine practice, we use tocilizumab for patients resistant to standard treatment with predominantly joint involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pro-inflammatory cytokines IL-1β, IL-6, TNF-α and IFN-γ markedly increased in sJIA patients and were closely related to the inflammation of sJIA [ 3 , 28 ]. Clinical trials showed that antibodies of these pro-inflammatory cytokines could effectively alleviate the disease severity in patients with sJIA [ 7 , 34 36 ]. Therefore, blocking these cytokines expression is a promising strategy for the development of novel anti-sJIA therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response in patients with systemic JIA was formally assessed according to the following response categories: 1) a good response, if the signs and symptoms of active disease (fever, rash, adenopathy, hepatosplenomegaly, serositis, and arthritis) had resolved and if the levels of inflammation markers (C‐reactive protein [CRP] and erythrocyte sedimentation rate [ESR]) had improved by at least 50% following treatment with anakinra and/or canakinumab, and if this response was maintained for at least 6 months; 2) a transient response, if there was an initial response characterized according to the parameters of a good response for at least 2 months but with later recurrence of disease; or 3) a poor response, if the parameters for improvement were not met. These treatment response criteria had been previously established for the purpose of a separate analysis of the AID registry cohort .…”
Section: Methodsmentioning
confidence: 99%